Consensus-Based Resilience Assurance for System of Systems - Huanjun Zhang; Yutaka Matsubara (IEEE Access)
The complexity of a System of Systems makes resilience one of its key attributes. Numerous studies have focused on the quantitative assessment of resilience by trailing indicators, yet discussions on resilience assurance through monitoring leading indicators remain scarce. Resilience assurance in SoS faces two major challenges: lack of structured argumentation work related to resilience and conflicts among multiple independent stakeholders. To address these challenges, this paper first introduces a resilience argumentation approach based on STAMP (Systems-Theoretic Accident Model and Processes), then employs cooperative consensus process model to seek consensus on resilience assurance. Additionally, under the requirements of the international standard IEC 62853 for open systems dependability, a consensus based resilience assurance framework is proposed. Within the framework, the resilient team can discuss the specific implementation details of failure response, accountability, and change accommodation based on stakeholder consensus. Finally, two SoS case studies, Microgrid and Mobility as a Service, are used to demonstrate the application of the proposed approach.